2003
DOI: 10.1063/1.1603078
|View full text |Cite|
|
Sign up to set email alerts
|

Marie Curie: In the Laboratory and on the Battlefield

Abstract: This year is the centennial of the Nobel Prize in Physics shared by Henri Becquerel and the Curies for their pioneering work on radioactivity. But Marie Curie’s contribution to the medical use of x rays is not widely known.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
4

Year Published

2011
2011
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 4 publications
0
3
0
4
Order By: Relevance
“…Biomedical images are referred to as "medical images". Which may be cytopathology and histopathology [134], ultrasound [135], X-rays [136], CT scans [137], MRIs [138], fNIR [139] and PET images [140].…”
Section: B Biomedical Imagingmentioning
confidence: 99%
“…Biomedical images are referred to as "medical images". Which may be cytopathology and histopathology [134], ultrasound [135], X-rays [136], CT scans [137], MRIs [138], fNIR [139] and PET images [140].…”
Section: B Biomedical Imagingmentioning
confidence: 99%
“…Analytical chemistry concepts have defined the quantitative analysis approach since fire assays were used to quantify the weight of gold (1375−1350 BC) 2 and have arguably been a fundamental part of modern medicine since before the 19th century, as Wilhelm Roentgen accidentally discovered X-rays 14 and Madame Marie Skłodowska Curie designed mobile radiograph units providing X-rays to hospitals. 15 There is a wide-ranging presence of analytical chemistry in patient care and analyses, including techniques such as magnetic resonance and spectroscopy (fluorescence spectroscopy; MRI; magnetic resonance spectroscopy, MRS; mass spectrometry of biomarkers; serum NMR analysis), radiation analysis (fluoroscopy; mammography; X-ray), and tomography (CT; PET; XRF-CT). 2 In investigative medical studies, to date, reviews of analytical chemistry topics in healthcare are scarcely observed in GOB-A textbooks (and courses that assign these texts).…”
Section: ■ Considerations Of Analytical Chemistry Topics In Health Sc...mentioning
confidence: 99%
“…É extensa a literatura sobre a vida e a obra do casal Marie e Pierre Curie, de modo que citamos as referências mais aderentes ao nosso trabalho [27,[33][34][35][36][37][38][39][40][41][42][43] Os registros históricos mostram, ainda, que na primavera de 1894 eles se conhecem. Em 26 de julho de 1895 eles se casam.…”
Section: A História Que O Filme Não Contaunclassified
“…Para quem conhece a história, trata-se de uma sequência bizarra. Ao nosso conhecimento, não há registro na literatura que indique a autenticidade dessa sequência [37,38,43,50]. O que se sabe é que no verão de 1914, Irène e Ève, acompanhadas de uma babá, estavam de férias em uma casa alugada na Bretanha, enquanto em Paris Marie enfrenta a burocracia e a falta de recursos para instalar equipamentos de raios-X a serem usados nas frentes de batalha.…”
Section: Sequência 8 (01:24:44958) -Irène Convence Marie a Se Envolve...unclassified